Plan de capacitaciones para el empoderamiento de la mujer rural de la asociación asoagrotoca (2021)
It is of vital importance that for every community that develops its commercial activity has a clear and defined organizational chart, as well as that ir possesses the roles and functions of each of its roles and functios of each of its positions, that is why this document reflects the work carried out in the municipality of it touches Cunuca village, in the association